Typification and nomenclatural clarifications of Mesembryanthemum purpurocroceum and M. insititium (Ruschioideae, Aizoaceae) - Jocou, Adriel Ian (2020)
The typification of the names Mesembryanthemum purpurocroceum and M. insititium are discussed. A neotype (illustration by Duncanson) and a lectotype (a specimen at B in Willdenow’s Herbarium) are designated. Epitypes (deposited at BOL) are also selected for both names. Nomenclatural issues about the specific epithet “purpurocroceum” are discussed. The two names are accepted here in Malephora as heterotypic synonyms, with M. purpurocroceum having nomenclatural priority. (Autor de correspondencia: adrieljocou@gmail.com)